Treatment of wastewater from rubber industry in Malaysia - Mohammadi, Mitra; Che Man, Hasfalina; Hassan, Mohd Ali; Phang, Lai Yee (Academic Journals, 2010)
Presently, Malaysia is the third largest rubber producer in the world, whereby the rubber industry is an economically and socially significant industry. Rubber industry consumes large volumes of water, uses chemicals and other utilities and produces enormous amounts of wastes and effluent. Discharge of untreated rubber effluent to waterways resulted in water pollution that affected the human health. With a new global trend towards a sustainable development, the industry needs to focus on cleaner production technology, waste minimization, utilization of waste, resource recovery and recycling of water. The present work aims at highlighting various technologies that currently have been used for treatment of rubber effluent in Malaysia. The work introduces the basis of these processes including their benefits and also problems. It also adheres to the future trends of rubber effluent treatment in Malaysia by reviewing various treatment technologies for natural rubber industry implemented by Thailand, the world largest rubber producer. These new and effective effluent treatment methods would minimize environmental pollution of rubber industry and bring it to become sustainable and environmental friendly.